Мой друг - пират - Гилкерсон Уильям (Клуб семейного досуга, 2008)
Экземпляры: ф.4 (20151116) / Инвентарный номер: 2520 / Цена: / Сис.шифр: 84(4Вел)-4 / Авт.знак: Г 47 / ГРНТИ: 17.82.31 / ББК: 84(4Вел)-44